Forecasting Practice and Perception of Forecasting in a Government-Funded Malaysian University - Aziz, Rozainun Abdul; Manap, Junaidah A. (JABM, 2008)
Many previous studies have concentrated more on using and improving tools of forecasting, however there is still the underlying doubt of forecasting function and where does it fit into the picture of management. This reservation is slowly receiving recognition in the forecasting literature. The objective of this study is to provide better insights into the practice of forecasting in a university scenario in Malaysia, a service industry as encouraged. A case study approach is employed on a Malaysian government-funded university through questionnaire and interviews. Our data analysis is qualitative and descriptive in nature, interpreting opinions of preparers and users of forecasts. Our findings unveil that the forecasting function currently used is a simple and straight-forward process. Preparers are unfamiliar with formal forecasting methods, though some are aware of the existence of certain methods and users prefer to read simple and easy to understand forecast figures. Towards achieving the status of a research university, it is now essential that the university emphasises forecasting in their planning function. It is hoped that this paper will elevate such a disposition and bring theory closer to practice as warranted by Shaw (2007) and Lawrence et al. (2006) in surfacing with value of forecasts.